Queer Jewish lives between Central Europe and Mandatory Palestine biographies and geographies - Afken, Janin 1980-; Brom, Dotan; Korbel, Susanne 1991-; Laskowski, Piotr‏ ‎ 1976-; Lavie, Hilla; Pretzel, Andreas 1961-; Rozin, Yael; Wolf, Benedikt 1985-; Yaal, Orit (transcript, 2022)
When queer Jewish people migrated from Central Europe to the Middle East in the late 19th and early 20th centuries, they contributed to the creation of a new queer culture and communality in Palestine. This volume offers the first collection of studies on queer Jewish lives between Central Europe and Mandatory Palestine (1870-1960). While the first section of the book presents queer geographies including Germany, Austria and Palestine, the second section introduces queer biographies between Europe and Palestine including the sexologist Magnus Hirschfeld (1868-1935), the writer Hugo Marcus (1880-1966), and the dance critic Giora Manor (1926-2005)
Keywords: Gender History; Gender Studies; Gender; Homosexuality; Jewish Studies; Mandatory Palestine; Migration; Postcolonialism; Queer Theory; Queer; Religion; HISTORY / Social History; Jewish gays; Aufsatzsammlung